Evaluation of Stuffing Out in the Warehouse PT. Lyon Oceanic Trans Surabaya - Vernandy, Anggy Ryo; Akhmad, Ekka Pujo Ariesanto; Hidayat, Sapit (Universitas Hang Tuah, 2024)
This study aims to evaluate the obstacles causing delays in the stuffing out process at the warehouse of PT. Lyon Oceanic Trans Surabaya. The research method used is a qualitative approach by collecting data through observations and in-depth interviews with warehouse workers and managers. The results show that the delay in stuffing out is caused by several main factors, namely the late delivery of goods from customers to the warehouse and the lack of support tools such as forklifts, thus relying only on human labor. The conclusion of this study indicates the need for increased efficiency in the delivery of goods as well as the addition of facilities and equipment in the warehouse to expedite the stuffing out process.